2020
DOI: 10.3329/agric.v18i1.49462
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Introducing Four Crops Based Cropping Patterns in Kushtia Area of Bangladesh

Abstract: The trial was conducted at Multi Location Testing (MLT) site under On-Farm Research Division, BARI, Kushtia during the last week of February, 2015 to second week of February, 2017 at farmers’ field condition to find out the productivity and profitability of three alternate cropping patterns, i.e. ACP1=Mustard (var: BARI Sarisha-15) - Mungbean (var: BARI Mung-6) - T. Aus rice (var: BRRI dhan48) - T. Aman rice (var: Binadhan-7), ACP2=Lentil (var: BARI Masur-6) - Mungbean (var: BARI Mung-6) - T. Aus rice (var: BR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Recent research found that a four crop-based cropping system, which includes Aus (pre-monsoon rice, Oryza Sativa L.), Aman (monsoon rice, Oryza Sativa L.), lentil (Lens culinaris), and mungbean (Vigna radiata), was more profitable than the double or triple crop cropping systems [3], and farmers can easily follow this new system. This newly adopted cropping system may increase farm income while creating job opportunities, alleviating poverty, and ultimately creating positive changes in the farmers' livelihoods.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research found that a four crop-based cropping system, which includes Aus (pre-monsoon rice, Oryza Sativa L.), Aman (monsoon rice, Oryza Sativa L.), lentil (Lens culinaris), and mungbean (Vigna radiata), was more profitable than the double or triple crop cropping systems [3], and farmers can easily follow this new system. This newly adopted cropping system may increase farm income while creating job opportunities, alleviating poverty, and ultimately creating positive changes in the farmers' livelihoods.…”
Section: Introductionmentioning
confidence: 99%